STRATEGIC DIRECTIONS OF ENTERPRISE MANAGEMENT IN THE GREEN ECONOMY - Ashurova Oltin Yuldashevna; Samadova Madina; Shadiqulova Aziza (Ecominds Press, 2025)
This scientific article explores comprehensive strategic directions for enterprise management within the evolving paradigm of the green economy, outlining how sustainability has become a core determinant of competitive advantage, operational resilience, technological modernization, and long-term financial viability. The study synthesizes theoretical insights, global policy dynamics, sector-level transformations, quantitative indicators, and case-based evidence to frame a holistic and integrated green management architecture suitable for diverse industries and national contexts. The research identifies how enterprises must redefine corporate strategies around decarbonization, circular economy principles, stakeholder-driven governance, resource efficiency, renewable energy adoption, eco-innovation, green marketing, green finance instruments, digital transformation, and environmental risk assessment.
Keywords: Green economy, enterprise management, strategic directions, sustainability, resource efficiency, ESG, circular economy, eco-innovation, environmental governance, renewable energy, sustainable development, green finance.